Do capital structure and cash holding expropriate minority shareholders? A case of non-financial concentrated firms in Pakistan. Issue 4 (10th June 2020) - Alim, Wajid; Kaleem, Muhammad; Abbas, Sammar; Khan, Dilawar
Abstract : Purpose: One aspect of agency theory suggests that dominant shareholders use the firm's assets for their personal benefits and 1thus expropriate minority shareholders (tunneling). Accordingly, this paper aims to examine the effect of capital structure and cash holding decisions on minority shareholders' expropriation for short and long periods. Design/methodology/approach: Data of 16 years (2000-2015) has been obtained from 200 non-financial firms registered at Pakistan Stock Exchange (PSX). The study used fixed effect and autoregressive distributed lagged to obtain the results. Findings: The results suggest that the presence of more debts in capital structure is positively associated with minority shareholders' expropriation, whereas a negative association has been found between the level of cash holding and minority shareholders expropriation. These results have been observed as significant both for the short and long run. Research limitations/implications: This study also suggests some important measures to control minority shareholders' expropriation by the dominant shareholders and thus to protect their rights. Originality/value: There is a lack of literature for this severe issue in the developing countries especially Pakistan, so this study narrates the potential measures to the regulatory authority of the market to curb tunneling and to protect minority shareholders.